2022
DOI: 10.5114/wiitm.2022.118776
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral versus unilateral radioactive stent insertion for hilar cholangiocarcinoma.

Abstract: Introduction: Radioactive stent insertion (RSI) is widely used for patients with obstructive hilar cholangiocarcinoma (HC) to increase the stent patency and overall survival (OS). However, one controversy of treating HC patients is determining whether to use unilateral or bilateral stenting. General knowledge on unilateral and bilateral RSI efficacy is still lacking. Aim: To evaluate the clinical efficacy and long-term prognoses of unilateral and bilateral RSI in HC patients. Material and methods: Between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The prognosis of MHO patients is generally poor, with a 5-year overall survival (OS) rate of less than 10% [3][4][5]. As patients suffering from MHO incidence are often diagnosed when the underlying disease has already reached an advanced stage, they are generally ineligible for surgical resection [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of MHO patients is generally poor, with a 5-year overall survival (OS) rate of less than 10% [3][4][5]. As patients suffering from MHO incidence are often diagnosed when the underlying disease has already reached an advanced stage, they are generally ineligible for surgical resection [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care options for MHO patients generally entail biliary stent insertion, which can rapidly alleviate jaundice and provide patients with the opportunity to undergo subsequent antitumour treatment [6][7][8]. Prior meta-analyses have suggested that bilateral stenting can achieve superior clinical success rates to those associated with unilateral stenting when treating MHO patients, while also lowering rates of stent dysfunction [9,10].…”
Section: Introductionmentioning
confidence: 99%